Plain language communication as a priority competency for medical professionals in a globalized world - Warde, Fiona; Papadakos, Janet; Papadakos, Tina; Rodin, Danielle; Salhia, Mohammad; Giuliani, Meredith (Canadian Medical Education Journal, 2018)
This brief report aims to highlight the impact of globalization – the international movement of goods, people, and ideas – on patient-provider communication in medical training and practice, and how the implementation of plain language communication training as a core competency for care providers can mitigate this impact. Globalization influences both patient and provider population diversity, which presents challenges with regard to patient-provider communication, particularly in cases of limited health literacy. Plain language communication - the delivery of information in a simple, succinct, and accurate manner - can help address these challenges. Training in plain language communication, however, is not a part of standard education for health care providers. Based on a synthesis of relevant literature pertaining to globalization, plain language communication, and medical education curricula, it is hoped that the information presented establishes the need for plain language communication as a core competency in medical education to enable providers to better meet the needs of an increasingly globalized health system.